The Effect of Calcusolâ„¢ to the Plasma Free Radical and Serum Creatinin in Mus Musculus Nephrolithiasis Model - Aâ€™liyatur Rosyidah; Sri Widyarti; Sri Rahayu (Journal of Tropical Life Science, 2013)
Calcusol is a traditional medicine (jamu) ade from Tempuyung (Sonchus arvensis) extract and is usually used for cure kidney stone disease. However, there has not been any studies which investigate the its mechanism. The aim of this study is to know the effect of Calcusolâ„¢ to the plasma free radical and serum creatinin of Mus musculus model for renal calcium-oxalate accumulation. This study is carried out by administration of Porang (Amorphophallus muelleri) tuber flour for 3 months with the doses 6 mg/100g BW to induce renal calcium oxalate accumulation and Calcusolâ„¢ treatment for 7 days with the doses of 3.3mg/g BW. Group I was used as a control group. Group II was only given porang (A. muelleri)every day for 3 months. Group III was only given Calcusolâ„¢ for 7 days. Group IV were given porang (A. muelleri) for 3 months then given Calcusolâ„¢ for 7 days. Group V were given porang (A. muelleri) and Calcusolâ„¢ simultaneously for 3 months. Porang and CalcusolTM is administrated orally. Blood was collected from the tail of theanimal for serum creatinin test and plasma free radical test using TBARS method. The data was analyzed using ANOVA followed by Tukey HSD to compare the means employing SPSS 16.0 forwindows. The result of the research shows that the treatment Calcusolâ„¢ on mice model for renal calcium oxalate accumulation. The content of MDA at group I, group II, group III, group IV and group V, respectivelyis 0.81±0.5 mg/ml; 2.63±0.8 mg/ml; 0.56±0.5 mg/ml; 2.09±0.9 mg/ml and 0.17±0.17 mg/ml. And the content of serum creatinine are 0.15±0.04 mg/dL; 0.13±0.03 mg/dL; 0.12±0.08 mg/dL; 0.11±0.016 mg/dL and 0.14±0.015 mg/dL at group I, group II, group III, Group IV, and group V respectively. This indicates that Calcusolâ„¢ decreases plasma free radical production during renal stone formation, while serum creatinin reduced but not significantly changed. Calcusolâ„¢ has an effect to decrease free radical during renalstone formation inmice model for calcium oxalate accumulation and also decrease serum creatinin.